2022
DOI: 10.1371/journal.pbio.3001609
|View full text |Cite
|
Sign up to set email alerts
|

Defining the determinants of protection against SARS-CoV-2 infection and viral control in a dose-down Ad26.CoV2.S vaccine study in nonhuman primates

Abstract: Despite the rapid creation of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) vaccines, the precise correlates of immunity against severe Coronavirus Disease 2019 (COVID-19) are still unknown. Neutralizing antibodies represent a robust surrogate of protection in early Phase III studies, but vaccines provide protection prior to the evolution of neutralization, vaccines provide protection against variants that evade neutralization, and vaccines continue to provide protection against disease severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 90 publications
1
16
0
Order By: Relevance
“…The identification of the RBD as the sole target of vaccine-elicited polyclonal antibodies broadly neutralizing SARS-CoV-2 variants is reminiscent of recent reports describing broadly neutralizing sarbecovirus monoclonal antibodies isolated from infected individuals (14 -16, 18, 20, 76-78, 93) and the rapid accumulations of mutations in the NTD (25,66,67,73,75). Although cross-variant plasma neutralization is determined by RBD-directed antibodies, we note that Fc-mediated effector functions, including antibody-dependent phagocytosis, cellular cytotoxicity, and complement activation, can play key roles for in vivo protection in addition to direct viral neutralization (94)(95)(96)(97)(98)(99). These findings motivate the clinical development of RBD-based vaccines against SARS-CoV-2 (37,(100)(101)(102)(103)(104) and sarbecoviruses (105)(106)(107)(108) for future pandemic preparedness.…”
Section: Discussionmentioning
confidence: 86%
“…The identification of the RBD as the sole target of vaccine-elicited polyclonal antibodies broadly neutralizing SARS-CoV-2 variants is reminiscent of recent reports describing broadly neutralizing sarbecovirus monoclonal antibodies isolated from infected individuals (14 -16, 18, 20, 76-78, 93) and the rapid accumulations of mutations in the NTD (25,66,67,73,75). Although cross-variant plasma neutralization is determined by RBD-directed antibodies, we note that Fc-mediated effector functions, including antibody-dependent phagocytosis, cellular cytotoxicity, and complement activation, can play key roles for in vivo protection in addition to direct viral neutralization (94)(95)(96)(97)(98)(99). These findings motivate the clinical development of RBD-based vaccines against SARS-CoV-2 (37,(100)(101)(102)(103)(104) and sarbecoviruses (105)(106)(107)(108) for future pandemic preparedness.…”
Section: Discussionmentioning
confidence: 86%
“…Once infection is established, Fc-mediated effector functions become more relevant to clear viral infections. Systemic serology approaches have even revealed that different antibody functions can contribute to various degrees to protection dependent on the viral pathogen, as shown for influenza viruses, RSV, or SARS-CoV-2 (36)(37)(38)(39). Passive immunization studies in animal models have further demonstrated that the degree of protection achieved by the application of mAbs depends on their IgG subclass (40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Although neutralizing activity of antibodies is a correlate of vaccine-mediated protection 4 , the ability of monovalent COVID-19 vaccines to protect against Omicron disease in the setting of waning serum antibody neutralization suggests additional protective immune mechanisms. These include anamnestic B cell responses that rapidly generate cross-reactive neutralizing antibodies, cross-reactive T cells responses, and/or non-neutralizing, cross-reactive antibodies that promote Fc mediated effector activities 6,16,18,38,39 . In our experiments, we focused on evaluating Fc mediated effector functions as a possible mechanism of vaccine-mediated protection against antigenic variants.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the loss in serum neutralizing activity against variants such as those in Omicron lineage, most individuals remain protected against severe disease and death. The basis for this protection has not been fully determined but could be due to beneficial effects of non-neutralizing antibodies, cross-reactive T cell responses, or anamnestic memory B cell responses 6,[15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%